2021
DOI: 10.1007/s00520-021-06203-y
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with non-metastatic breast cancer: evolution during follow-up and vulnerability factors

Abstract: Objective In women with breast cancer, many disease-related psychosocial factors directly affect quality of life (QoL) during and after treatment. The aims of this prospective study were to evaluate the psychosocial factors affecting QoL and its dimensions, to study their evolution over time, and to determine the factors associated with this evolution. Methods Thirty women with non-metastatic breast cancer were asked to complete a number of questionnaires evaluating QoL and its dimensions, symptoms of anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Hence, functional connectivity results at T1 and across T1 and T2 suggest that, before chemotherapy but also more pervasively across the cancer trajectory, BC patients might be less sensitive than HC to somatosensory information. This hypothesis fits with previous reports showing changes in the relationship BC patients have with their body (Helms et al, 2008;Lantheaume et al, 2021;Sebri et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Hence, functional connectivity results at T1 and across T1 and T2 suggest that, before chemotherapy but also more pervasively across the cancer trajectory, BC patients might be less sensitive than HC to somatosensory information. This hypothesis fits with previous reports showing changes in the relationship BC patients have with their body (Helms et al, 2008;Lantheaume et al, 2021;Sebri et al, 2021).…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have shown that higher self‐esteem is an important indicator for better quality of life. In some patients, cancer and its treatments can lead to lower self‐esteem and disturb patients' relationship with their body and with others, which in turn can negatively impact quality of life (Helms et al, 2008; Lantheaume et al, 2021; Sebri et al, 2021). As a life‐threatening illness, cancer is related to many stressful events that may lead to psychosocial changes such as those involving self‐representations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this linked data source captures both HRQoL data and tumor information. Additionally, this study is among the first to examine HRQoL over a 2-year period following HR+ eBC diagnosis, which is important since HRQoL can change over time ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify the duration and components of an intervention program that supports the transition from cancer patients to survivors, empirical evidence needs to be accumulated through an integrated investigation of changes in the QOL of breast cancer patients and the factors affecting these changes [ 6 , 7 ]. In previous studies, factors affecting the QOL of breast cancer survivors included physical and psychological symptoms, self-efficacy [ 7 9 ], and social support [ 10 12 ]. The greater the symptoms experienced by breast cancer patients, the higher the psychological distress level, the lower their physical and social functioning, and the worse the overall QOL [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy positively affects the QOL of breast cancer survivors by helping them actively cope with cancer-related health problems [ 9 ] and maintaining self-management and health behavior for various symptoms [ 14 ]. Social support is also a representative environmental factor affecting the QOL of breast cancer patients; the provision of sufficient social support, such as feeling protected or receiving help from others [ 15 , 16 ], assists survivors in actively coping with health problems [ 17 ] and finding positive meaning in life [ 18 ], which ultimately improves their QOL [ 10 , 12 , 16 ].…”
Section: Introductionmentioning
confidence: 99%